Comparison between growth performance in two silvopastoral systems comprising trees, short-lived perennial shrub, a forage, and livestock) (Research, Society and Development, 2021)
We aim to determine the growth performance of two 20-year-old silvopastoral systems comprising two timber trees, a palm tree), a short-lived perennial shrub, a forage and livestock; and to investigate fibre features and certain physical and mechanical properties of two timber trees (Myracrodruon urundeuva and Peltophorum dubium) in two plantation systems. The first system is called MP with two timber trees and the second one is called MPS with two timbers and a palm tree. The studied systems showed that it was possible to successfully combine fast-growing species, animals, forage and woody tree species, with a production cycle of more than 50 years of different goods and services (e.g., ornamentals, palm hearts, landscaping, fruits, seeds, bee pasture, meat, and wood). The height, diameter and volume for M. urundeuva trees in the MP system were greater than in the MPS system, whereas no difference between the systems was observed for P. dubium. By comparison, the growth and volume in P. dubium were greater than in M. urundeuva. For wood properties, it was shown that both systems can be used successfully, but the MPS system performed better than the MP system, in the aim of wood production of high mechanical strength and calorific value. In addition, the MPS intercropping system can yield more goods and services than the MP system, both systems bring returns with short-term (bean seed, forage, pasture), medium-term (forage, palm products, pasture, wood), and long-term (wood) financial returns.